2007
DOI: 10.1007/s00606-007-0577-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic studies on two F1 hybrids of autotetraploid rice varieties showing extremely high level of heterosis

Abstract: Abstract. Mechanisms of two F1 hybrids (D46A · DTP-4 and D46A · Dminghui63) of autotetraploid rice (2n = 4x = 48) showing extremely high pollen fertility 87.40% and 85.97%, respectively, seed set 82.00% and 79.00%, respectively and extremely high level of heterosis were analyzed cytologically. The chromosome pairing of D46A · DTP-4 and D46A · Dminghui63 was normal at metaphase I(MI), and had almost no I or III, with an average of 0.020I +14.36 II 6.44rod+7.91ring) +0.01III + 4.80 IV + 0.01VIII and 0.06 I + 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Long et al (2007) considered that the autotetraploid rice maintainer lines with more number of quadrivalents exhibited more stable inheritance than the autotetraploid rice restorer lines, and believed that the increase in quadrivalents results in good chromosome pairing of maintainer lines. High percentage of trivalents and univalent were generally resulted in low seed setting of autotetraploid plants (Cai et al, 2007;Luan et al, 2007;He et al, 2011a,b;Wu et al, 2014). In our study, more number of quadrivalents were found in newly developed autotetraploid rice 1162 than that in its parents with low seed setting, while the frequency of trivalent and univalent was lower in the new line comparing with its parents at diakinesis and metaphase I.…”
Section: Low Trivalent and Univalent Might Be The Main Reason For Higsupporting
confidence: 44%
See 2 more Smart Citations
“…Long et al (2007) considered that the autotetraploid rice maintainer lines with more number of quadrivalents exhibited more stable inheritance than the autotetraploid rice restorer lines, and believed that the increase in quadrivalents results in good chromosome pairing of maintainer lines. High percentage of trivalents and univalent were generally resulted in low seed setting of autotetraploid plants (Cai et al, 2007;Luan et al, 2007;He et al, 2011a,b;Wu et al, 2014). In our study, more number of quadrivalents were found in newly developed autotetraploid rice 1162 than that in its parents with low seed setting, while the frequency of trivalent and univalent was lower in the new line comparing with its parents at diakinesis and metaphase I.…”
Section: Low Trivalent and Univalent Might Be The Main Reason For Higsupporting
confidence: 44%
“…Abnormal meiosis chromosome behavior, such as multivalents and univalents, happened frequently in autotetraploid plants, and was considered important reasons for low seed setting of the autotetraploids (Luan et al, 2007;Long et al, 2007;He et al, 2011a,b). Multivalents of chromosome included trivalents, quadrivalents, pentavalents, and so on, in autotetraploid plants.…”
Section: Low Trivalent and Univalent Might Be The Main Reason For Higmentioning
confidence: 99%
See 1 more Smart Citation
“…Autotetraploid rice has four sets of homologous chromosomes, and chromosome behaviour is more complicated in autotetraploid rice than in the diploid counterpart. Abnormal chromosome behaviour is a major reason for pollen abortion in autotetraploid rice (Luan et al 2007, 2009; He et al 2011a, b; Wu et al 2014). There are many types of abnormal chromosome behaviour in the autotetraploid rice, including chromosome straggling and chromosome lagging (Wu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Autotetraploid rice (2 n = 4 x = 48) derived from diploid rice (2 n = 2 x = 24) through chromosome doubling with colchicine is an excellent pool for desirable genes for resistance to pathogens and high protein content (Luan et al. 2007).…”
mentioning
confidence: 99%